2022
DOI: 10.13189/saj.2022.100216
|View full text |Cite
|
Sign up to set email alerts
|

Development of Early Childhood Skills by Guiding Tests in Sports Rhythmic Gymnastics

Abstract: When compared to the previous youths, especially before the pandemic, younger generations have become sedentary globally. However, the truth is physical activity positively contributes to human growth and development by causing both physiological and psychological benefits. In the wake of revitalizing such benefits, this current study aimed to develop a guidebook containing physical activity tests that should be implemented in primary schools for early childhood through rhythmic gymnastic sport. This study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…Strength and conditioning is described as a systematic and purposeful activity involving bodily movements that are planned, structured, and repetitive, with the aim of maintaining or improving physical fitness, overall health, and well-being. Essentially, the strength and conditioning includes a diverse range of exercises encompassing cardiovascular, strength, speed, flexibility, and endurance components, tailored to individual needs, decrease injury risk, and goals (Balyi et al, 2013;Bompa & Buzzichelli, 2015;González et al, 2022;Ilham & Dimyati, 2021;Mario et al, 2022;Sukarmin et al, 2021;Sulistiyowati et al, 2022;Zouhal et al, 2010). The development of physical fitness components such as endurance, strength, speed, and flexibility plays a crucial role as determinants of fitness performance and chosen sports skills (Bahtra et al, 2020;Balyi et al, 2013;Bompa & Buzzichelli, 2015;Chaeroni et al, 2022;Donie et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Strength and conditioning is described as a systematic and purposeful activity involving bodily movements that are planned, structured, and repetitive, with the aim of maintaining or improving physical fitness, overall health, and well-being. Essentially, the strength and conditioning includes a diverse range of exercises encompassing cardiovascular, strength, speed, flexibility, and endurance components, tailored to individual needs, decrease injury risk, and goals (Balyi et al, 2013;Bompa & Buzzichelli, 2015;González et al, 2022;Ilham & Dimyati, 2021;Mario et al, 2022;Sukarmin et al, 2021;Sulistiyowati et al, 2022;Zouhal et al, 2010). The development of physical fitness components such as endurance, strength, speed, and flexibility plays a crucial role as determinants of fitness performance and chosen sports skills (Bahtra et al, 2020;Balyi et al, 2013;Bompa & Buzzichelli, 2015;Chaeroni et al, 2022;Donie et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The capacity for kinesthetic empathy, the ability to mentally embody actions, highlights the profound human connection achieved through physical observation (Davidson, 2021). It is important to note that advancing to the highest level of performance requires mastering fundamental movements and specific sports skills that engage the entire body (Sulistiyowati et al, 2022). Research has shown that educational interventions can enhance muscle endurance, strength, and the activation of electromyography (EMG) in muscles supporting the spine, pelvis, and hip area.…”
Section: Introductionmentioning
confidence: 99%